Biodiesel production from reutealis trisperma oil using conventional and ultrasonication through esterification and transesterification - Riayatsyah T.M.I.; Thaib R.; Silitonga A.S.; Milano J.; Shamsuddin A.H.; Sebayang A.H.; Rahmawaty; Sutrisno J.; Mahlia T.M.I. (MDPI AG, 2023)
biofuel; catalyst; concentration (composition); environmental impact; ester; fossil fuel; methanol; optimization; sulfuric acid; ultrasonics; Reutealis trisperma